EMPOWERMENT OF THE KEREKAN VILLAGE COMMUNITY THROUGH PROCESSING EMPRIT GINGER INTO GINGER SHAKE - Shofuria Shofuria; Dahlia; Ali Rohmat; Roma Wijaya (khidmatan, 2023)
The large potential of the number of emprit ginger plants grown by villagers can be optimized as a ginger beverage product that has the potential to improve their welfare. This initiative can serve as an effective home-based processing enterprise in reducing unemployment, increasing individual income, and stimulating economic growth in the region, thereby harmonizing economic development between rural and urban areas. The main objective of this community service project is to empower the community in Kerekan Hamlet by processing emprit ginger into ginger shake drinks. The approach applied is Participatory Action Research (PAR), which involves the community as partners in all stages of the activity, from problem identification to the end of implementation. During the mentoring, the materials taught included an understanding of the health benefits of ginger, which requires further processing to produce various variants of ginger products. The results of this community service indicate that assistance in processing ginger emprit products can generate new business opportunities that can stimulate community economic growth.